Performance of Beting Bamboo (Gigantochloa Levis) as partial replacement for coarse aggregate in concrete - Md. Kassim, Tahara Ramadzan; M H, Hasnan; N Z N, Azizan (IOP Publishing Ltd, 2021)
Conventional construction materials are considered as exploitation to natural resources. Thus, numerous alternative materials using natural or waste materials are proposed for concrete production as a response for greener, renewable and biodegradable environments with regard to sustainability. Natural fibre such as bamboo has been rapidly proposed for many applications especially for concrete production in construction. In order to tackle the environmental issues and focusing on sustainability, natural fibre of Beting bamboo is proposed for partial replacement used as supplementary cementitious materials. Current study investigates the partial replacement of coarse aggregate with Beting bamboo in concrete mixtures. The outcome of the study discovers that through the mix design, replacing 5% by weight of Beting bamboo is an ideal % to achieve concrete mixture for structural and nonstructural application. However, with the increase % of Beting bamboo for partial replacement, the strength of the concrete gradually decreased.